2021
DOI: 10.1007/s00265-021-03044-x
|View full text |Cite
|
Sign up to set email alerts
|

Male aggressiveness and risk-taking during reproduction are repeatable but not correlated in a wild bird population

Abstract: The existence of among-individual variation in behaviour within populations is poorly understood. Recent theory suggests that fine-scale individual differences in investment into current versus future reproduction may lead to a ‘slow-fast’-pace-of-life continuum, also referred to as the ‘pace-of-life-syndrome’ (POLS) hypothesis. According to this idea, individuals are predicted to differ in their level of risk-taking, which may drive among-individual variation and covariation of behaviours. Consistent individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 87 publications
1
6
1
Order By: Relevance
“…Indeed, our results are in line with previous results on aggression in female great tits 7 , 19 . Moreover, studies on male aggression during simulated territorial intrusions in another blue tit population reported even higher repeatability (R = 0.56 23 ) compared to our observations in females. Yet another study on blue tits found that the repeatability of female nestling defence and handling aggression to be equal or higher, respectively, to that of males 6 , suggesting potential sex and/or population dependent variability in the repeatability of aggression.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Indeed, our results are in line with previous results on aggression in female great tits 7 , 19 . Moreover, studies on male aggression during simulated territorial intrusions in another blue tit population reported even higher repeatability (R = 0.56 23 ) compared to our observations in females. Yet another study on blue tits found that the repeatability of female nestling defence and handling aggression to be equal or higher, respectively, to that of males 6 , suggesting potential sex and/or population dependent variability in the repeatability of aggression.…”
Section: Discussioncontrasting
confidence: 83%
“…repeatable) between-individual variation in behaviour is commonly referred to as a personality trait 21 , 22 . Several studies have shown that intrasexual aggression and hissing are repeatable behaviours, with evidence of consistent individual variation in intrasexual aggression observed in various taxa, including a number of songbirds (reviewed in Salazar et al 23 ). While fewer studies have focussed on hissing behaviour, it has also been found to be individually consistent in female great tits, highlighting the recognition of these traits as aspects of animal personality 5 , 19 .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, our study does not indicate that singing effort is related to the studied fitnesstraits in the aquatic warbler. Although in some songbirds it was found that repeatability of the repertoire size is greater than expected by chance (Naguib et al 2019;Salazar et al 2021), future studies on the aquatic warbler should attempt to establish variation in song traits more precisely, e.g. by recording males repeatedly within a season, and to cover more breeding seasons.…”
Section: Discussionmentioning
confidence: 97%
“…However, our study does not indicate that singing effort is related to the studied tness-and quality-traits in the aquatic warbler. Although in some songbirds it was found that repeatability of the repertoire size is greater than expected by chance (Naguib et al 2019;Salazar et al 2021), future studies on the aquatic warbler should attempt to establish variation in song traits more precisely, e.g. by recording males repeatedly within a season, and to cover more breeding seasons.…”
Section: Discussionmentioning
confidence: 97%